Cystoisosporiosis in a patient from San Pedro, Lara State, Venezuela (Salud, Arte y Cuidado, 2018)
We present the case of female patient with Cystoisosporiosis, diagnosed by direct stool examination, where Cystoisospora belli Oocysts with sporoblast were observed inside, treated with Metronidazole, presenting clinical and parasitological cure